Perancangan Media Pembelajaran Menggunakan Autoplay pada Mata Pelajaran Animasi 2 Dimensi di SMKN 1 Rao Selatan Kabupaten Pasaman - Harahap, Ahmad Gunawan; Zakir, Supratman (Indonesian Research Journal on Education, 2022)
The research was conducted because the author found several problems at SMK N 1 RAO SELATANduring the learning process of 2-dimensional animation subjects. Among them are still limited learning media used in 2-dimensional animation learning, namely "still in the form of modules and no application-based learning media, and many students who do not understand the material presented. From this problem, the researchers designed learning media using Autoplay on the subject of 2- dimensional animation at SMKN 1 RAO SELATAN KAB. PASAMAN is valid, practical, and effective. The results of the media learning in the form of a desktop application can provide benefits to students where students can study anywhere and anytime by only using a laptop/PC. The research method used is Research and Development (R&D) with a 4-D research model with the stages of define, design, development, and dissemination. In the Development stage, the media development stage is carried out using Auto play. The model of media development used in this research is Luther-Sutopo's version of MDLC (Multimedia Development life cycle), which consists of 6 stages, namely conceptualization, design, material collection, manufacturing process, testing and distribution. The results of this study are exe products with a validity test result of 0.80 which is declared valid, a practicality test result is 0.91 which is stated to be very practical, and an effective test result is 0.88 and is declared very effective. With these results it can be guaranteed that with this Auto play learning media it is valid, practical, and effective.